2009
DOI: 10.1186/1471-2180-9-182
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a salt-induced DhAHP, a gene coding for alkyl hydroperoxide reductase, from the extremely halophilic yeast Debaryomyces hansenii

Abstract: BackgroundDebaryomyces hansenii is one of the most salt tolerant species of yeast and has become a model organism for the study of tolerance mechanisms against salinity. The goal of this study was to identify key upregulated genes that are involved in its adaptation to high salinity.ResultsBy using forward subtractive hybridization we have cloned and sequenced DhAHP from D. hansenii that is significantly upregulated during salinity stress. DhAHP is orthologous to the alkly hydroperoxide reductase of the peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 45 publications
(55 reference statements)
2
18
0
Order By: Relevance
“…We assume that NaCl stress leads to oxidative stress; it can then be expected that 3.5 m NaCl leads to a higher level of ROS, just as it occurs during oxidative stress where ROS levels increase as the oxidant increases. However, another important factor in the ROS generation is the exposure time; Knöbel et al () showed in human cells exposed to ferric nitrilotriacetate (Fe‐NTA) that ROS generation is time and dose dependent, which may explain why our results are similar to those reported by Chao et al ().…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We assume that NaCl stress leads to oxidative stress; it can then be expected that 3.5 m NaCl leads to a higher level of ROS, just as it occurs during oxidative stress where ROS levels increase as the oxidant increases. However, another important factor in the ROS generation is the exposure time; Knöbel et al () showed in human cells exposed to ferric nitrilotriacetate (Fe‐NTA) that ROS generation is time and dose dependent, which may explain why our results are similar to those reported by Chao et al ().…”
Section: Discussionsupporting
confidence: 88%
“…They found an upregulation of genes known to express under osmotic stress; genes related to protein synthesis and maintenance and, remarkably, genes related to mitochondrial functions. Chao et al () reported DhAHP as a novel gene that significantly conferred salt stress tolerance in this yeast; they also found that the overexpression of DhAHP , an alkyl hydroperoxide reductase, diminished the accumulation of reactive oxygen species (ROS) under hypersaline stress and that repression of DhAHP expression decreased the tolerance to salt stress. Lately, it was reported that NaCl protects against oxidative stress in D. hansenii (Navarrete et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…According to studies from the literature, overexpression of the homologous 2-Cys Prx gene encoding ubiquitous thiol-specific peroxidases increased stress tolerance and redox homeostasis in several organisms. For example, salt-induced Debaryomyces hansenii AHP (DhAHP, Prx isoform) expression conferred higher salt tolerance by reducing the cellular ROS level in D. hansenii, S. cerevisiae, and Pichia methanolica (Chao et al 2009). Overexpression of A. thaliana 2-Cys Prx (At2-Cys Prx; accession no.…”
Section: Discussionmentioning
confidence: 99%
“…Gene DhAHP1 , coding for a cytosolic alkyl hydroperoxide reductase, is regulated under saline conditions, and the corresponding protein has been also correlated with salt resistance (Chao et al , ). Silencing of its expression in D. hansenii resulted in decreased tolerance, while overexpression, both in S. cerevisiae and in D. hansenii , conferred enhanced tolerance to salinity.…”
Section: Genes Involved In Osmotic Stress Response and Cation Homeostmentioning
confidence: 99%
“…Silencing of its expression in D. hansenii resulted in decreased tolerance, while overexpression, both in S. cerevisiae and in D. hansenii , conferred enhanced tolerance to salinity. The fact that overexpressing transformants exhibited reduced levels of reactive oxygen species (ROS) under salt stress suggests that DhAhp1 may play a key role in adaption to high salinity by scavenging ROS, serving as chaperone and mediating oxidative stress signalling (Chao et al , ).…”
Section: Genes Involved In Osmotic Stress Response and Cation Homeostmentioning
confidence: 99%